2010
DOI: 10.1097/mph.0b013e3181d74702
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib Plus Valproic Acid for Infant Spinal Glioblastoma

Abstract: Spinal glioblastoma multiforme (GBM) is rare in children. New therapeutic options should be explored given the poor outcomes reported. We describe the case of an infant with spinal GBM whose condition worsened despite radiotherapy and chemotherapy. Immunohistochemical analysis of the tumor sample showed activation of the Raf-MEK-ERK pathway. Targeted pharmacologic therapy with sorafenib plus valproic acid led to decrease in the size of the tumor and improvement of symptoms. We conclude that regulation of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Valproic acid exhibits anticancer potential through causing cell growth arrest, differentiation, autophagy, and apoptosis. In addition, it resensitizes cancer cells to treatment by conventional antineoplastic agents , . Moreover, valproic acid also exerts cytoprotective effects and suppresses apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…Valproic acid exhibits anticancer potential through causing cell growth arrest, differentiation, autophagy, and apoptosis. In addition, it resensitizes cancer cells to treatment by conventional antineoplastic agents , . Moreover, valproic acid also exerts cytoprotective effects and suppresses apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…the use of therapeutic agents which act upon inhibit growth factor receptors; receptors present both on the glioma cell and the tumor endothelial cells. 29,30 However, no Phase I trial as yet has shown a highly significant prolongation of patient survival using novel signal modulatory drugs. We performed animal studies using an invasive GBM isolate which expresses the constitutively active form of the EGF receptor (ERBB1 vIII).…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic significance of the KIAA1549:BRAF fusion, if any, is still unclear, although a few studies have found no differences in survival between tumors with and without BRAF duplication/fusion (28, 42, 45, 48). Nevertheless, the frequent BRAF alteration in PA I may serve as a novel therapeutic target for pharmacological inhibition of the MAPK pathway, particularly in tumors that are difficult to fully excise surgically (75, 78, 88). Previous in vitro studies have revealed that stable silencing of BRAF through lentiviral transduction with inhibition of Map/Erk kinase (MEK)1/2 blocked proliferation and arrested growth of glioma cells (73).…”
Section: Braf Fusionsmentioning
confidence: 99%